PcrA-mediated disruption of RecA nucleoprotein filaments—essential role of the ATPase activity of RecA - Fagerburg, Matt V. (Oxford University Press, 2012)
The essential DNA helicase, PcrA, regulates recombination by displacing the recombinase RecA from the DNA. The nucleotide-bound state of RecA determines the stability of its nucleoprotein filaments. Using single-molecule fluorescence approaches, we demonstrate that RecA displacement by a translocating PcrA requires the ATPase activity of the recombinase. We also show that in a ‘head-on collision’ between a polymerizing RecA filament and a translocating PcrA, the RecA K72R ATPase mutant, but not wild-type RecA, arrests helicase translocation. Our findings demonstrate that translocation of PcrA is not sufficient to displace RecA from the DNA and assigns an essential role for the ATPase activity of RecA in helicase-mediated disruption of its filaments.